Civil Protection of Generative AI - Hazem Akram Salal; Faris Kamel Hassan (Journal of Legal Sciences, 2024)
The tremendous advancements in the field of Generative AI have raised questions about how to legally protect the content produced by such systems and who owns its rights. Opinions differ regarding the possibility of granting artificial intelligence legal personality—a concept signifying its recognition as an entity capable of acquiring rights and bearing obligations. However, this proposal faces numerous legal challenges, primarily the absence of awareness and discernment in intelligent systems, which are often essential prerequisites for any legal responsibility. Consequently, this notion remains largely a subject of theoretical debate rather than practical application at present. Yet, to assert its improbability in the future is to veer far from accuracy. Since intellectual property laws are considered a realistic framework for protecting AI content, where rights are attributed to the owner or designer of the program, these laws face challenges such as determining responsibility for violations (the programmer, the owner company, or the user), the originality of the resulting content, and whether it is considered a creative work worthy of protection. The solution lies in updating the laws to keep pace with the development of artificial intelligence, which ensures a balance between innovation and protection of rights.